2007
DOI: 10.1094/phyto-97-5-0632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Phytophthora ramorum by Real-Time Polymerase Chain Reaction Using TaqMan, SYBR Green, and Molecular Beacons

Abstract: Bilodeau, G. J., Lévesque, C. A., de Cock, A. W. A. M., Duchaine, C., Brière, S., Uribe, P., Martin, F. N., and Hamelin, R. C. 2007. Molecular detection of Phytophthora ramorum by real-time polymerase chain reaction using TaqMan, SYBR Green, and molecular beacons. Phytopathology 97:632-642.Sudden oak death, caused by Phytophthora ramorum, is a severe disease that affects many species of trees and shrubs. This pathogen is spreading rapidly and quarantine measures are currently in place to prevent dissemination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 54 publications
(72 reference statements)
1
66
0
Order By: Relevance
“…Improved specificity would allow undiluted extracts from cultures to be tested without the risk of false-positive results. One approach to improving the discrimination of similar species is to design a new assay for a different region of the genome (2,13,29). However, modifications to existing assays can also be made to improve specificity without the need to completely redesign the primers and/or probe.…”
mentioning
confidence: 99%
“…Improved specificity would allow undiluted extracts from cultures to be tested without the risk of false-positive results. One approach to improving the discrimination of similar species is to design a new assay for a different region of the genome (2,13,29). However, modifications to existing assays can also be made to improve specificity without the need to completely redesign the primers and/or probe.…”
mentioning
confidence: 99%
“…In this study, the sensitivity of Molecular beacon and TaqMan probes against a dilution series of P. fragariae genomic DNA was equivalent (Bonants et al 2004). Also, Bilodeau et al (2007) compared three different chemistries including SYBR Green, TaqMan, and Molecular beacons using sequences of β-tubulin, ITS and elicitin gene regions for detection of P. ramorum causing sudden oak death. The results showed that all three real-time PCR assays could separate the pathogen from 65 other species of Phytophthora in all infected samples.…”
Section: Detection Of Plant Pathogensmentioning
confidence: 99%
“…Many PCR assays were developed for P. ramorum (e.g. Tomlinson et al 2007;Bilodeau et al 2007;Tooley et al 2006;Martin et al 2004;Hughes et al 2006;Hayden et al 2006), to the point of causing some confusion in the international regulatory community as to which one should be routinely used. The international ring trial to evaluate several of these methods simultaneously with the same samples should become a model for other pathogens ).…”
Section: Diagnostics and Molecular Detectionmentioning
confidence: 99%